Ecological Momentary Assessment of the Quality of Life and Self-Efficacy Among People With a Stoma: Longitudinal Study - William Goodman; Matthew Allsop; Amy Downing; Julie Munro; Gill Hubbard; Rebecca J Beeken (Journal of Medical Internet Research)
Abstract BackgroundWhen a stoma is formed, people with a stoma have to adjust to managing this on a daily basis. There are a number of factors that can impact their self-efficacy to self-manage and their quality of life, including complications with their stoma, body image concerns, stigma, and the changes to their daily routine. Ecological momentary assessment studies in other populations have suggested that these constructs may vary over short periods of time and could be influenced by contextual factors. We, however, do not currently understand how context-specific factors such as what an individual is doing, who they are with, or where they are could impact upon quality of life and self-efficacy in people with a stoma. ObjectiveThis study aimed to understand whether quality of life and self-efficacy fluctuated over time and whether contextual factors (eg, activity, location, or company) and time of day were associated with quality of life and self-efficacy over the course of a week. MethodsA smartphone-based ecological momentary assessment study was conducted over a 7-day period with measurements taken 3 times a day (morning, afternoon, and evening). Measures included demographic and clinical characteristics of age, gender, and time with a stoma, and self-reported self-efficacy and quality of life in the moment rated from 0 to 100 (with 100 being the best). Multilevel modeling was conducted due to the clustering of responses within individuals, with models run for both self-efficacy and quality of life. ResultsIn total, 62 participants completed the ecological momentary assessment protocol. Null multilevel models indicated that both self-efficacy and the quality of life varied over time, with around 35% of total variance explained by within-person variability, which suggests that there are intraindividual fluctuations over time. Results indicated that, for the self-efficacy model, people reporting from home had higher levels of self-efficacy than those outside the home (βββ ConclusionsTo the best of our knowledge, this is the first study to use ecological momentary assessment in this population. These findings indicate that, among people with a stoma, self-efficacy and quality of life do vary from moment to moment. Furthermore, contextual factors such as location and time of day are associated with self-efficacy and quality of life. There is a need to explore how future self-management interventions could enhance self-efficacy to self-manage outside of the home environment, with the potential for more dynamic and tailored interventions.